THE ANALYSIS OF THE TRAINING NEEDS OF HUMAN RESOURCES IN THE ROMANIAN SECONDARY EDUCATION SYSTEM - Mariana POPA (PETRESCU) (Management & Marketing)
The continuous training of the teaching, guidance and control staff is based both on the compliance with the qualitative and professional standards and with the competencies that are specific to the profession and is achieved through: training programmes for the granting of the teaching degrees, training courses, re-training programmes, study programmes in a specialization other than the one previously obtained by the teaching staff in the secondary education system, etc. The acquisition of new knowledge by the teaching staff participating in professional training programmes, re-training or professional improvement programmes is closely related to the improvement of the teaching process by implementing in the teaching act the newly acquired knowledge, innovative teaching methods, the enhancement of creativity in the creation of new teaching materials and the approach of modern teaching methods and techniques. The training of the teaching staff must take into account the developmental need of the educational establishments while also meeting the needs for change of the environment in which the educational system pursues its activity